Quantum sensitivity of squeezed Schrodinger cat states - Ranjit Singh; Alexander E. Teretenkov (Physics Open, 2024)
Theoretically it is shown that high quantum sensitivity of the squeezed state of the Schrodinger cat relative to the non-squeezed state can be achieved. For realization of squeezing the Schrodinger cat state, a parametric process in a nonlinear optical crystal is used. To visualize the squeezed state of the Schrodinger cat with and without a displacement, the values of the Wigner functions are calculated.